Control de Spodoptera frugiperda utilizando dósis de Ciromazina y Clorpirifos mezcladas con arena en el cultivo de maíz (Zea mays L.), en la zona de Ventanas - Moreno Macías, Daniel (2011)
This research work was carried out near the parish of the canton Pechiche Puerto Ventanas Los Rios province, between 18 February and 20 June 2010, the area has a humid tropical climate with annual temperature of 26 ° C with a average annual rainfall of 2115.9 mm / year. In the experimental plot has irregular topography with a regular drain, we used the hybrid INIAP 551 is called experimental design used randomized blocks with 12 treatments and 3 replications was used multiple range test of Tukey at 5% probability. The treatments investigated were: Chlorpyrifos 100 cc / ha + Arena, Chlorpyrifos 200 cc / ha + Arena, Chlorpyrifos 300 cc / ha + Arena, Chlorpyrifos 500 cc / ha + Arena, Ciromizina 10 g / ha + Arena, 20 g Cyromazine / ha + Arena, Cyromazine 30 g / ha + Arena, Cyromazine 50 g / ha + Arena, Chlorpyrifos 1 l / ha + Water, Cyromazine 50 g / ha + Water, and just sand. Larval populations were assessed, percentage of plants attacked, attacked percentages of ears, plant height, number of ears per plant, cob size, number of rows of kernels per ear, weight of 100 grains and yield.